First chemoenzymatic stereodivergent synthesis of both enantiomers of promethazine and ethopropazine - Borowiecki, Paweł; Paprocki, Daniel; Dranka, Maciej (Beilstein Journal of Organic Chemistry, 2014)
Enantioenriched promethazine and ethopropazine were synthesized through a simple and straightforward four-step chemoenzymatic route. The central chiral building block, 1-(10H-phenothiazin-10-yl)propan-2-ol, was obtained via a lipase-mediated kinetic resolution protocol, which furnished both enantiomeric forms, with superb enantioselectivity (up to E = 844), from the racemate. Novozym 435 and Lipozyme TL IM have been found as ideal biocatalysts for preparation of highly enantioenriched phenothiazolic alcohols (up to >99% ee), which absolute configurations were assigned by Mosher’s methodology and unambiguously confirmed by XRD analysis. Thus obtained key-intermediates were further transformed into bromide derivatives by means of PBr3, and subsequently reacted with appropriate amine providing desired pharmacologically valuable (R)- and (S)-stereoisomers of title drugs in an ee range of 84–98%, respectively. The modular amination procedure is based on a solvent-dependent stereodivergent transformation of the bromo derivative, which conducted in toluene gives mainly the product of single inversion, whereas carried out in methanol it provides exclusively the product of net retention. Enantiomeric excess of optically active promethazine and ethopropazine were established by HPLC measurements with chiral columns.
Keywords: ethopropazine; lipase-catalyzed kinetic resolution; Mosher methodology; promethazine; stereodivergent synthesis